PENGUKURAN KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN ANALISIS RASIO AKTIVITAS - MOH. KHOIRUL GHUFRON; Moh. Herman Djaja; Adriani - Kusuma; Wahyu - Maulana (Universitas Madura, 2024)
In a company there is a mechanism for creating a mission, vision and company motto. Each company has a different mechanism to achieve this. The company's most important orientation is to collect as much profit as possible for the sustainability of the company. If a company is able to compete in the world of market economy, then the company will be able to survive in today's developments and technology. Financial performance in managing company finances is very vital for the company. Good financial performance will keep the company moving and operating. For this reason, this activity ratio is really needed by companies because this ratio explains the company's effectiveness in managing existing resources. Each activity ratio has its own function. So when the company is considered effective if all the characteristics of the activity ratio have reached the company's standard values.